The Effect Of Innovation Strategy On Competitive Advantage In Creative Industry (Case Study Of Msmes In The Field Of Handicrafts In The City Of Surabaya) - Mohammad Afrizal Miradji; Agung Riyanto; Yovio Annisa Rahmadhoni; Rizky Pratama Lafizha Putra; Nofan Aldiansyah (Sean Institute, 2024)
Abstract is Creative industry is one of sector that has rapid development in Indonesia, especially in Surabaya. The part of this sector that tends to decrease every year or have smallest development level is Handycrafts. Although the number of businessman in this part is less than in food and beverage part, the competition between them is also fierce. The businessman should be the one who can decide the proper competitive strategy to survive in this competition. The other way to do to win the competition is applying innovation strategy towards the product so that it can be different from our competitor products and attract more customers. This research determined the relationship between innovation strategy and competitive advantage in the SME handycraft business in Surabaya. Linear regression will be used for determine this relationship.